The Evolution of Accounting Information Systems Research: a 10-Year Bibliometric Analysis - Muhammad Pondrinal; Asniati Bahari; Rita Rahayu; Verni Juita (Universitas Batanghari Jambi, 2026)
This study provides a comprehensive bibliometric assessment of Accounting Information Systems (AIS) research spanning 2016-2025, utilizing Dimensions.ai as the primary data source and VOSviewer for scientific mapping. A total of 4,041 publications were retained after structured filtering procedures. Temporal analysis indicates accelerated growth in AIS scholarship, largely driven by the integration of enterprise technologies, cloud infrastructures, and data-centric decision frameworks. Network visualizations highlight the United States as the epistemic core of AIS research, exhibiting superior productivity and collaboration metrics, while emerging contributions from Asia signal developing regional research clusters. Institutional analysis reveals concentrated knowledge production within leading global universities, whereas journal density mapping underscores the multidisciplinary diffusion of AIS discourse. Citation network analysis identifies seminal works that serve as intellectual anchors within the field. These findings collectively underscore the expanding theoretical boundary and technological orientation of AIS. Future research should advance inquiries into automation, AI-enabled accounting systems, digital audit ecosystems, and cross-institutional research synergies to strengthen the field’s scientific maturity.